Evaluation of Helicobacter pylory colonization by serologic test (IgG) and dyspepsia in volunteers from the countryside of Monte Negro, in the Brazilian western Amazon region - Ribeiro, Rafael Bernardon; Martins, Herlon Saraiva; Santos, Vera Aparecida dos; Khouri, Marcelo el; Duarte, Leandro Savoy; Burattini, Marcelo Nascimento; Cordeiro, Quirino; Camargo, Luiz Marcelo Aranha; Corbett, Carlos Eduardo Pereira (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
The present study intended to analyze the seroprevalence of Helicobacter pylori, IgG, and its relation to dyspepsia in a population from the western Amazon region. During the "Projeto Bandeira Científica", a University of São Paulo Medical School program, in Monte Negro's rural areas, state of Rondônia, 266 blood samples were collected from volunteers. The material was tested for IgG antibodies anti-Helicobacter pylori by ELISA method and the participants were also interviewed on dyspepsia, hygiene and social aspects. Participants aged between five and 81 years old (34 years on average), 149 (56%) were female and 117 (44%) male. We found 210 (78.9%) positive, 50 (18.8%) negative and six (2.3%) undetermined samples. Dyspeptic complaints were found in 226 cases (85.2%). There was no statistical association between dyspepsia and positive serology for H. pylori. We concluded that the seroprevalence in all age categories is similar to results found in other studies conducted in developing countries, including those from Brazil. On the other hand, the seroprevalence found in Monte Negro was higher than that reported in developed countries. As expected, there was a progressive increase in the positivity for H. pylori in older age groups.